Interfacial reactions and microstructure related properties of explosively welded tantalum and steel sheets with copper interlayer. (October 2021) - Paul, H.; Chulist, R.; Lityńska-Dobrzyńska, L.; Prażmowski, M.; Faryna, M.; Mania, I.; Szulc, Z.; Miszczyk, M.M.; Kurek, A.
Graphical abstract: Highlights: The melted areas at the Ta/Cu interface are composed of a mixture of pure Cu and Ta. The solidified melts are softer than strain-hardened layers of steel. Melted zones are formed via solidification of the systems showing miscibility gap. Recovery and recrystallization occurs already during clad manufacturing. Abstract: This paper presents a comprehensive study of the microstructure-property relationships in Ta and stainless or carbon steel composites, fabricated by explosive welding using Cu interlayer. Employing scanning (SEM) and transmission (TEM) electron microscopy and X-ray synchrotron diffraction, a complex microstructure of interfacial layers was examined. Particular attention was placed on the description of the phase transformation mechanisms in the reaction regions, and the competition between the strain-hardening and softening processes in parent sheets. SEM and TEM analyses showed that Cu and Ta nanoparticles, and small dendrites, dominated the reaction regions near the Ta/Cu interfaces, whereas the nano-grained phases having more complex chemical compositions were identified near the Cu/steel interfaces. SEM orientation mapping revealed that the interfacial layers of the parent sheets underwent severe plastic deformation as a result of dislocation slip, twinning, and shear banding. Such heavily deformed areas can easily undergo recovery and recrystallization already during clad processing. In consistence with these findings, the micro-hardness values of the welded sheets increased as the joining interface approached, except for the layers directly adhering to large reaction regions, where a decrease in micro-hardness was observed. However, the solidified melt regions were essentially softer than the strain-hardened layers of both steels. Based on experimental results a new explanation for the reaction region formation was proposed and a significant modification of the description of the interfacial microstructure of parent sheets was done. Finally, the effect of microstructural changes on the clads properties was discussed.